Case report: Minimally invasive management of synchronous early-stage ascending colon adenocarcinoma and type 1 papillary renal cell carcinoma presenting with severe anemia: a rare Chinese case - Li, Jiahao; Guo, Kai; Yi, Li; Yuan, Chenrong; Tang, Ningjuan; Wu, Simei; Zhu, Yongdong; Tan, Yue; Wang, Zhi; Yang, Wanyong; Zhu, Yuanzan; Tian, Yu; et al. (Frontiers in Oncology, 2026)
BackgroundAscending colon adenocarcinoma(ACA) synchronous with papillary renal cell carcinoma (pRCC) is extremely rare, with only sporadic cases reported in the literature around the world. The oncogenic mechanisms, early diagnosis, and minimally invasive treatment of the coexistence of ACA and pRCC face significant challenges. This article describes a case diagnosed with concurrent ACA and pRCC at early-stage presented with severe anemia were successfully treated in a primary care centers in China.Case presentationA 66-year-old male with abdominal distension, fatigue, and weakness lasting over 1 month was presented to our outpatient clinic. Laboratory tests revealed severe anemia, while imaging examination were highly suspicious for both colon cancer and renal carcinoma. Colonoscopy confirmed the presence of a mass in the ascending colon, and the biopsy results suggested adenocarcinoma. Then, after a multidisciplinary discussion, blood transfusion and iron therapy were applied to improve the anemia, then the patient underwent laparoscopic radical right hemicolectomy and left kidney lesion resection surgery under general anesthesia. Postoperative pathology revealed ACA and type 1 pRCC. The patient subsequently received postoperative chemotherapy etc, and the prognosis was favorable.ConclusionSynchronous ACA with type 1 pRCC are extremely rare. The early stage diagnosis and minimally invasive treatment of the concurrent ACA and pRCC was still challenges. Preoperative anemia improvement, laparoscopic tumor resection combined with postoperative chemotherapy etc is an important treatment strategy for early-stage ACA and pRCC, as it allows for the simultaneous radical resection of tumors in both locations. The multidisciplinary management model is crucial for the personalized treatment of patients with complex malignancies in primary care center.